DESAIN SIMPLE DAN MODERN DALAM PERANCANGAN WEBSITE PENJUALAN - Indahsari, Rina dewi; setyati, Endang (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
Interface design can not be deceptive, because it is seen as the first one in any aplication. Attractive website interface design will provide a tremendous effect toward the users. Beside website facilities and systems, interface design also be considered by website users. This study will scope how to design interface website by chosing layout, colour and simple or modern typography style. This style is chosen because it represents the characteristics of human lifestyles recently, who always want any things easely, fastly and futuristic. Designing layout is concerning on design principles such as balance, proportion and unity, and so on. Keywords: design, simple modern, website